Design of a novel microtubule targeted peptide vesicle for delivering different anticancer drugs. Issue 48 (6th May 2016) - Adak, Anindyasundar; Mohapatra, Saswat; Mondal, Prasenjit; Jana, Batakrishna; Ghosh, Surajit
Abstract : A novel microtubule targeted peptide vesicle has been designed and developed for delivering both hydrophilic and hydrophobic drugs. It delivers both the drugs close to their intracellular targets, shows significant anticancer effect in both 2D monolayer and 3D spheroid cells. Abstract : A microtubule targeted peptide-based delivery vehicle has been designed using two oppositely charged peptides, which targets tubulin/microtubules, delivers both hydrophilic and hydrophobic drugs into their target site through lysosome at acidic pH. Drug loaded vesicles show a significant anticancer effect compared to control drugs in a 2D monolayer and a 3D spheroid cell.